Rejection of the Cigarette Billboard Sampoerna A Mild “Mula Mula Malu-Malu, Lama Lama Mau” - Donna Carollina (IJCAS (International Journal of Creative and Arts Studies), 2016)
In early 2015, a billboard advertisement of cigarette product Sampoerna A Mild titled “Mula Mula Malu-Malu, Lama Lama Mau” or in English means “Initially Feel Shy, Gradually Want” were protested by the majority of Indonesian people. Protests were stated on the website www.change.org, with a petition asking for the billboard to be removed immediately. Shortly after, Sampoerna A Mild company responded to the protest by apologizing to the people of Indonesia and removing the billboard. This case raises several questions for the author: Why was Sampoerna A Mild’s billboard removed?; What were the communicative sign contained in the illustrations that causes the billboard to be removed?; What was the idelogical background of Indonesian society which causes them to reject the billboard of Sampoerna A Mild? To answer these questions, this research based on a case study uses the methods of art critic as described by E.B Feldman. Data collection was done based on the study of literature, then the findings were analyzed inductively. Results of research revealed that the billboard was removed because it was considered a pornographic illustration. Pornography as seen in the communicative sign illustration of a young couple hugging each other, as well pornography in the illustration which includes the text that reads “Mula Mula Malu-Malu, Lama Lama Mau” or “Initially Feel Shy, Gradually Want”. The majority of Indonesian society rejected the billboard of Sampoerna A Mild and considered the billboard illustration to contain pornography due to their ideological background which is based on ethics and morality of Indonesian culture. Therefore, that rejection of the billboard is mainly due to an illustration displaying things that are in violation of Indonesian culture.